Perception about electronic waste: case study in a Federal Education Institution (Research, Society and Development, 2020)
With the increasing generation of solid waste in Brazil and in the world, the correct and conscious disposal of these types of materials has been increasingly challenging. The impacts are diverse, whether environmental, economic, social or cultural. The present study sought to identify the students' perception of the integrated courses of Electro-electronics Technician, Technician in Maintenance of Heavy Machines, Technician in Mechanics and Technician in Environment of the IFPA campus Parauapebas regarding electronic waste. The research was carried out in three stages, the first consisting of a bibliographic survey. In the second stage, on-site observation was carried out, as well as the application of a semi-structured questionnaire, and the third stage consisted of tabulation and analysis of the data obtained. The research is classified as quali-quantitative, considering that in addition to investigating whether professionals are aware of what is being investigated, it is proposed to collect data in relation to their level of knowledge. From the study it was found that the knowledge of students at the IFPA campus Parauapebas is unsatisfactory, there was a high degree of ignorance regarding the disposal of electronic waste. Only the result of the landfill receiving e-waste was satisfactory in relation to the knowledge of the institution's students, 100% of the students know that e-waste cannot be discarded in the landfill. For the applicable and applicable solution in the studied region, there must be a stricter inspection in local companies. In addition, it is necessary to implement e-waste collection points on the IFPA campus in Parauapebas.